THE DEVELOPMENT OF INTRODUCTION TO ESSAY WRITING COURSE’S TEXTBOOK BASED ON HOTS-TECH INTEGRATED WITH CM-PBL (CASE METHOD-PROJECT BASED LEARNING) - Muhammad Fatkhu Arifin; Candradewi Wahyu Anggraeni; Mercya Christ Sita Dewi (Premise: Journal of English Education and Applied Linguistics, 2023)
This study aims to develop Introduction to Essay Writing Course’s textbook based on HOTS-Tech integrated with CM-PBL (Case Method-Project Based Learning).This study uses the Research and Development method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) in developing the Introduction to Essay Writing textbook based on HOTS-Tech integrated with CM-PBL. There are several steps that must be passed to develop the textbook.The long-term goal of this research is the existence of theoretical, pedagogical and practical benefits. Theoretically, this research will examine and link theories to develop the Introduction to Essay Writing textbook based on HOTS-Tech integrated with CM-PBL. Pedagogically, this research contributes to lecturers, especially lecturers in writing courses, to develop the Introduction to Essay Writing Course Textbook. Practically, this research contributes to students using the Introduction to Essay Writing textbook based on HOTS-Tech integrated with CM-PBL as a learning support. This research will produce mandatory and additional outputs, the mandatory outputs of this research are scientific publications in national journals and Introduction to Essay Writing textbook based on HOTS-Tech integrated with CM-PBL which has ISBN. The additional output of this research is the Intellectual Property Right (HKI) of the Introduction to Essay Writing Textbook.